2018
DOI: 10.1029/2018gl080262
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Loss of Relativistic Electrons by EMIC Waves in the Outer Radiation Belt Observed by Arase, Van Allen Probes, and the PWING Ground Stations

Abstract: There has been increasing evidence for pitch angle scattering of relativistic electrons by electromagnetic ion cyclotron (EMIC) waves. Theoretical studies have predicted that the loss time scale of MeV electrons by EMIC waves can be very fast, suggesting that MeV electron fluxes rapidly decrease in association with the EMIC wave activity. This study reports on a unique event of MeV electron loss induced by EMIC waves based on Arase, Van Allen Probes, and ground‐based network observations. Arase observed a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 37 publications
(50 reference statements)
3
35
0
Order By: Relevance
“…Recently, REP events have been considered one of the fundamental loss processes of outer radiation belt electrons (Kubota et al, 2015;Kurita et al, 2018;Lorentzen et al, 2000;Millan et al, 2002). A basic understanding of REP events thus contributes to predicting the dynamic variation of the radiation belts, which is a major target of space weather forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, REP events have been considered one of the fundamental loss processes of outer radiation belt electrons (Kubota et al, 2015;Kurita et al, 2018;Lorentzen et al, 2000;Millan et al, 2002). A basic understanding of REP events thus contributes to predicting the dynamic variation of the radiation belts, which is a major target of space weather forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many reports of simultaneous observations of EMIC waves and the precipitation of relativistic electrons (Hirai et al, 2018;Kurita et al, 2018;Miyoshi et al, 2008;Rodger et al, 2008Rodger et al, , 2015. There have been many reports of simultaneous observations of EMIC waves and the precipitation of relativistic electrons (Hirai et al, 2018;Kurita et al, 2018;Miyoshi et al, 2008;Rodger et al, 2008Rodger et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, EMIC waves are thought to be more effective on the precipitation of relativistic electrons. There have been many reports of simultaneous observations of EMIC waves and the precipitation of relativistic electrons (Hirai et al, 2018;Kurita et al, 2018;Miyoshi et al, 2008;Rodger et al, 2008Rodger et al, , 2015. The quasi-linear theory is widely used for estimating the influence of the wave-particle interaction (Summers, 2005) and derives the timescale of the interaction as minutes to hours (Li et al, 2014;Ni et al, 2015;Summers et al, 2007;Ukhorskiy et al, 2010;Usanova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similar signatures were observed by Zhu et al (2020) and shown to be a result of nonlinear interaction between rising tone EMIC waves and MeV electrons, which can scatter particles toward the loss cone via phase trapping. Kurita et al (2018) also observed scattering of lower pitch angle MeV electrons in association with EMIC wave activity. This event suggests that while short-lived, these structured EMIC wave bursts can have rapid nonlinear scattering effects on energetic electrons, as demonstrated theoretically by Omura and Zhao (2012).…”
Section: Magnetospheric Responsementioning
confidence: 84%